Recurrent Giant Malignant Phyllodes Tumor of the Breast - Erik Kudela; Karol Kajo; Erik Kozubik; Tomas Rokos; Terezia Pribulova; Jan Danko; Eva Kudelova; Igor Homola; Pavol Slavik; Barbora Macurova; Kamil Biringer (Case Reports in Obstetrics and Gynecology)
Phyllodes tumors (PTs) are rare fibroepithelial neoplasms of the breast. They have a proliferating stromal component that can be graded as benign, borderline, and malignant. In addition, they are associated with an increased risk of local recurrence and distant metastasis. The authors hereby present a case report of a 34-year-old woman with recurrent malignant PT with an increasing aggressiveness. There were two recurrences of giant tumors that consumed the entire right breast, which developed over a three-year period. The final surgical treatment was a total extirpation of the tumor with subsequent plastic reconstruction using a cutaneous flap from the region of the latissimus dorsi muscle. The patient died three months after the last recurrence due to multiorgan failure.